Association Between Participation in HIV/ AIDS Peer Group, Stigma, Discrimination, and Quality of Life of People Living with HIV/ AIDS - Mia Ashari Kurniasari; Bhisma Murti; Argyo Demartoto (Journal of Epidemiology and Public Health, 2016)
Background: The quality of life of people living with HIV/ AIDS (PLH) is of public health concern and calls for attention. The quality of life of PLH may be affected by stigma and discrimination. Peer group of PLHs may have an important role in improving the quality of life of PLHs. This study aimed to investigate the association between participation in HIV/ AIDS peer group, stigma, discrimination, and quality of life of PLHs.Subjects and Method: This was an analytic and observational study with cross sectional design. This study was conducted in Tulungagung, East Java, from November, 2016 to January, 2017. A total of 65 PLHs participating in HIV/ AIDS peer group and 35 PLHs not participating in HIV/ AIDS peer group were selected for this study by  fixed exposure sampling. The dependent variable was quality of life of PLHs. The independent variables were participation in HIV/ AIDS peer group, stigma, and discrimination. The data were collected by a set of questionnaire and analyzed by path analysis model.Results: Participation in HIV/ AIDS peer group (b=0.27; p=<0.001), social support (b=0.43; p=<0.001), and family support (b=0.18 p=0.021), had positive associations with a decrease in stigma and discrimination towards PLHs. Higher income (b=0.33; p=0.026), higher education level (b=0.21; p=<0.001), less stigma and discrimination (b=0.33; p=<0.001), had positive associations with quality of life of PLHs. Core self evalution  showed positive association with quality of life of PLHs (b=0.31; p=<0.001).Conclusion: Participation in HIV/ AIDS peer group, social support, and family support, are positively associated with a decrease in stigma and discrimination towards PLHs. Higher income, higher education, less stigma and discrimination, are positively associated with quality of life of PLHs. Core self evalution is positively associated with quality of life of PLHs.Keywords: HIV/ AIDS peer group, stigma, discrimination, social support, family support, quality of lifeCorrespondence: Mia Ashari Kurniasari. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: Deandagelis@gmail.com. Mobile: 0851216175293.Journal of Epidemiology and Public Health (2016), 1(2): 125-132https://doi.org/10.26911/jepublichealth.2016.01.02.06